# Find the Relation Between a, b and c :

If 3(a^{2}+b^{2}+c^{2}) = (a+b+c)^{2}, then the relation between a, b and c is

- a=b≠c
- a≠b≠c
- a≠b=c
- a=b=c

**Answer is (4): a=b=c**

**Explanation:-**3 (a

^{2}+ b

^{2}+ c

^{2}) = (a + b + c)

^{2}

If we put a = b = c

Then, the value of 3 (a

^{2}+ b

^{2}+ c

^{2}) = (a + b + c)

^{2}

3 (a

^{2}+ a

^{2}+ a

^{2}) = (a + a + a)

^{2}

3 (3 a

^{2}) = (3a)

^{2}

9 a

^{2}= 9 a

^{2}

Then, the relation between a, b and c is a = b = c.

Hence, the answer is (4) a = b = c